Multi objective performances optimization of hybrid rotary ultrasonic assisted micro drilling on chemically strengthened glass - Abd. Rasid, Muhamad Firdauz (2021)
The usage of chemically treated strengthened glass has become a revolutionary and steadily increased for the past decade, predominantly by the electronic devices industry. Chemically treated strengthened glass offered a great strength as a result of a post-production chemical process by means of an ion-exchange process that improved scratching, impact and bending strength, as well as increased temperature stability which makes it as a preferred material for electronic panel display devices application such as mobile phone and tablet PCs screen, camera lens, optical component and many more. In such aforementioned applications, micro holes drilling is required to serve for particular purposes such as camera lenses, speakers and proximity sensors. However, due to the inherent properties of chemical treated toughened glass, stronger under compressive stress and weak under tension, it is a challenge for the subsequent secondary manufacturing process such as hole drilling. Conventional drilling process towards this glass tends to generate high tensile stress that consequently affects the hole performances and accuracy. This study proposed a significant advancement in improving the hole drilling quality using a hybrid machining technique. The hybrid technique combines two of established machining processes into a new combined setup known as Rotary Ultrasonic Assisted Drilling (RUAD). In order to obtain desired drilling quality specifications, namely, hole quality (burr area), and drilling thrust force, the ultrasonic machining and amplitude function performances are investigated. The Burr shape characterization and quantification are processed using the JAVA digital image processing software ImageJ, which is captured using the optical microscope (EMZ-13T Meiji Techno). Meanwhile, the thrust force measurement will be obtaining using kistler dynamometer (9257 B) The machine parameter, namely cutting speed in the range of 1000-3500 rpm, feed rate (0.5-1 mm/min), ultrasonic frequency ranging between 20 and 27 kHz, and amplitude (1-3 μm), were used. The aluminium oxide (Al2O3) slurry was applied within the machining ultrasonic environment. The 5% of concentration slurry circulated inside a designated slurry pool. The electroplated diamond tool was used to perform the drilling process. The experimental run based on the statistical Taguchi matrix was executed, comprising a different machining parameter. The further investigation proceeded by using statistical Response Surface Methodology for finding the best set of optimal machining parameter and satisfactory validation index. Based on the compromises decision between the responses on cutting speed and feed rate, the optimized parameter of drilling CSG glass was selected is 6511 rpm and 0.50 mm/min under RUAD condition of 27 kHz (ultrasonic frequency) and 1 μm (amplitude), with with the highest desirability index with 97.5%. The responses which are the burr area accuracy entry and exit with the machining trust force having relative percentage error with1.03%, 0.99%, and 0.37% respectively compared to prediction model values. Besides, the analytical results demonstrated that, the presence of the intermittent ultrasonic vibration amplitude was able to minimize the chipping area and enhance the hole quality with acceptable tolerance value.